Measuring the effectiveness of communication of a podcast on food sustainability - Pinto, Bruno; Matias, Ana; Granado, António (Frontiers in Communication, 2024)
In this study, the effectiveness of communication of a podcast was assessed regarding the variables knowledge retention and interest. Two podcast episodes were produced about Portuguese research in sustainable food, and two news pieces with similar information and reading times were written to be used as a control for this experiment. Initially, 115 students from two universities in Lisbon filled in an online pre-test questionnaire. One week later, 102 students from those 115 students initially assessed listened to one podcast or read one news piece and completed an online post-test questionnaire. Statistical analysis showed a significant increase in the knowledge retention in both media and no significant differences in what concerns interest on food sustainability or science. Moreover, it was found that there were no significant differences between the two tested media in both the knowledge retention and interest. Nevertheless, the recent popularity of podcasts may justify its production as a new and flexible way to communicate science.